Value at Risk Essays on banking and insurance sectors before and during COVID-19 - European Companies - Ritto, Rita Vieira Santos Korrodi (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management